BDY623: Global Biodiversity / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2019)
This course will discuss the human-nature relationship, and the uses and values of biodiversity. The focus will be the current issue in global biodiversity conservation initiatives particularly in areas with species and habitats under threat. This course explores questions of environmental justice for local communities where there are initiatives for global biodiversity conservation and networks of protected areas.